Small loans, big dreams : Muhammad Yunus, Grameen Bank and the microfinance revolution - Counts, Alex (The University Press Limited, 2025)
Microfinance—providing affordable loans and other financial services to help the poorest people lift themselves out of poverty—was pioneered by the Grameen Bank in Bangladesh. In 2006, the bank and its founder, Muhammad Yunus, were jointly awarded the Nobel Peace Prize, and microfinance has since gone on to serve over 100 million people—mostly women—on five continents. Small Loans, Big Dreams is an account of the origins and development of microfinance, from the $27 in loans given by a young economics professor to liberate poor villagers from loan sharks to its present status as a sometimes-controversial global phenomenon.